Theoretical study of the Sb-substitution effect on the optoelectronic properties of Cs2AgBiBr6 double perovskite - Lhouceine Moulaoui; Abdelhafid Najim; Marouane Archi; Mohamed Al-Hattab; Omar Bajjou; Anass Bakour; Youssef Lachtioui; Khalid Rahmani; Bouzid Manaut (Results in Chemistry)
We analyzed the structure of the double perovskite Cs2AgBiBr6 utilizing Density Functional Theory (DFT), adding different doping concentrations of the Sb atom (Cs2AgBi1-x SbxBr6, with x = 0.0625, 0.125, 0.1875). The investigation concentrated on the electronic structure of both pure and doped configurations, emphasizing the total density of states (TDOS) and the atomic orbital densities for each structure. The pure structure exhibits a maximum absorption coefficient of 7.65 × 104 cm−1 at a wavelength of 285 nm. Furthermore, we assessed multiple optical properties including reflectivity (R), absorption coefficient (α), refractive index (n*), dielectric function (ε), optical conductivity (σ), and loss function L(ω). The findings demonstrate that Sb doping diminishes the bandgap energy and increases the absorption coefficient in the visible spectrum. The enhancements indicate that Sb-doped Cs2AgBiBr6 hold significant potential for photovoltaic (PV) applications.